Efficacy and safety of Jinhuang ointment in treating acute gouty arthritis: a retrospective cohort study - Wang, Honglin; Mei, Huiling; Duan, Yuyu; Hua, Wei; Xu, Aoshuang; Lu, Lin (Frontiers in Pharmacology, 2025)
ObjectiveNon-steroidal anti-inflammatory drugs (NSAIDs) for acute gout often carry risks of gastrointestinal adverse effects and hepatic, renal, and cardiovascular toxicity. To explore safer treatment options and reduce the use of these drugs and associated risks, this study aimed to evaluate the clinical efficacy and safety of external application of Jinhuang Ointment in the treatment of acute gouty arthritis, providing evidence for optimizing clinical management strategies.MethodsA total of 104 patients with acute gouty arthritis (July 2023–June 2024) were retrospectively assigned to three groups: the control group (n = 35) received conventional Western therapy (celecoxib, low-purine diet, >2000 mL daily water intake, and sodium bicarbonate); T1 group (n = 35) received conventional therapy plus topical diclofenac diethylamine emulsion; T2 group (n = 34) received conventional therapy plus Jinhuang Ointment. All patients completed 7-day treatment. Baseline data including demographic characteristics, gout history, serum uric acid levels, onset time, and target joint distribution were collected. Primary outcome indicators, including pain improvement, joint tenderness, swelling, and joint mobility in the target joint. Secondary outcomes covered changes in serum uric acid levels and inflammatory markers (CRP, ESR). Adverse events occurring during the treatment period were also documented.ResultsBaseline characteristics were comparable across groups. After treatment, all groups showed significant improvements in VAS scores, joint swelling, tenderness, and mobility (P < 0.05). The T2 group exhibited a significantly shorter time to pain improvement compared to both the T1 and control groups (P < 0.05). Both T1 and T2 groups showed better outcomes in joint tenderness, swelling, and joint mobility than the control group (P < 0.05), though only T2 demonstrated significant superiority in swelling reduction (P < 0.05). Laboratory results indicated that CRP and ESR decreased more markedly after treatment in T1 and T2 than in controls (P < 0.05), with no intergroup difference in uric acid reduction. Adverse event rates were similar among groups, with no significant differences observed.ConclusionJinhuang Ointment combined with conventional therapy significantly improves joint pain and swelling, accelerates symptom relief, and exhibits particular efficacy in swelling reduction, without increasing safety risks. Its multi-component, multi-target mechanism provides a potential explanation for the clinical efficacy observed, thereby supporting the need for higher-quality studies to further verify its application value.